CURRICULUM MANAGEMENT OF BUIN BATU ELEMENTARY SCHOOL - Habiburrahman, Habiburrahman (JERAM, 2017)
The focus of this research is to study about the curriculum management at the Elementary School of Buin Batu that includes the curriculum planning, curriculum organization, curriculum implementation, and curriculum evaluation. It is a Case Study Research using a qualitative approach. Data obtained through in-depth interviews, observation and documentation with the research informants comprising the school principal, academic coordinator and curriculum coordinator. The data collected was analyzed through the process of data reduction, display, verification and conclusion drawing. The results of the research show that the Elementary School of Buin Batu has a curriculum planning that consists of Curriculum Mapping, Scope and Sequence, Program of Inquiry, Unit of Inquiry, and Unit Planner; a curriculum organization that includes Curriculum Structure, Teacher Assignment, Developing Transdisciplinary Program, Determining Unit of Inquiry for Each Year Level; a curriculum implementation that includes Teaching and Learning Experiences, Assessment and Reporting; and a curriculum evaluation that covers Unit Review and Subject Review. Keywords: curriculum management, curriculum planning, curriculum organization, curriculum implementation, curriculum evaluation